2013
DOI: 10.1007/s00248-013-0240-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Methicillin-Susceptible Staphylococcus aureus ST398 and ST133 Strains in Gut Microbiota of Healthy Humans in Spain

Abstract: Fecal samples of 100 healthy humans were tested for Staphylococcus aureus recovery. Fifteen samples (15 %) contained S. aureus, all methicillin-susceptible (MSSA), being one isolate/sample further studied. These 15 isolates were characterized by spa and agr typing as well as multi-locus sequence typing. High diversity of spa types (n = 11) and sequences types (n = 8) was detected. Two S. aureus of lineages ST398 or ST133 were detected, and six isolates were ascribed to clonal complex 30 (CC30). Strains were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…This genetic lineage has been previously reported in canine samples from Japan 29 and the absence of the genes of IEC system points to a possible animal origin of the strain. 13 In the same line, detection of one MSSA strain typed as t2678-ST133-CC133 is remarkable because in previous studies it has been detected in small ruminants such as goats or sheep. 30 The detection of gene lukM, prevalent in ungulates, ruminants and bovine mastitis, 7 and the absence of IEC genes, supports the idea of the possible animal origin of the strain.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This genetic lineage has been previously reported in canine samples from Japan 29 and the absence of the genes of IEC system points to a possible animal origin of the strain. 13 In the same line, detection of one MSSA strain typed as t2678-ST133-CC133 is remarkable because in previous studies it has been detected in small ruminants such as goats or sheep. 30 The detection of gene lukM, prevalent in ungulates, ruminants and bovine mastitis, 7 and the absence of IEC genes, supports the idea of the possible animal origin of the strain.…”
Section: Discussionmentioning
confidence: 92%
“…Seven of the spa types identified in this study were ascribed to CC30, a lineage frequently found as colonizer of human microbiota, 13,27 and it is also considered one of the most frequent S. aureus lineages detected in human infections. 3 Strains of skin origin of lineage CC30, recovered from the individual of case 4, harbored the tsst-1 gene encoding the toxic shock syndrome toxin (TSST).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is also active on some human leukocytes at higher concentrations than for other leukotoxins and α-toxin. These observations may raise questions about the role of this toxin into the bacterial pathogeny [151][152][153][154].…”
Section: Luke-lukd Leukotoxinmentioning
confidence: 96%
“…Seventeen virulence genes were analyzed using polymerase chain reaction (PCR) in recovered S. aureus isolates (16). The genes and the encoded virulence factors tested were Panton-Valentine leukocidin (lukF/lukS-PV); toxic shock syndrome toxin (tsst-1); exfoliative toxins A, B, and D (eta, etb, etd, respectively); alpha-, beta-, delta-, gamma-, and gamma-hemolysin variant (hla, hlb, hld, hlg and hlgv, respectively); leukocidins DE and M (luk-DE and lukM, respectively); aureolysin (aur); biofilm-associated protein (bap); adhesion factor (cna); and enterotoxin B and C (seb and sec, respectively).…”
Section: Microbiologic Analysismentioning
confidence: 99%